Study of Science Process Skills Student Using Worksheet based on Science Process Skills - Muhammad Khairul Wazni; Baiq Fatmawati (Jurnal Penelitian Pendidikan IPA, 2022)
The science process is related to cognitive development because it needs to be applied in the skills learning process to support students' mastery of science concepts which can provide better learning outcomes. The focus of this research is to develop a worksheet based on science process skills on biology content for the first grade of high school. Research design is research and development which consists of defining, designing, and developing. The participants for this preliminary field testing were twelve second-grade high school students at I.T Dhia'ul Fikri Sukarara, East Lombok. Collecting data using worksheets refers to science process skills indicators consisting of observation, classification, prediction, communication, and inference. The results of preliminary field testing were analyzed descriptively quantitatively by giving a score of 3, 2, and 1 for each of science process skills indicators, then percentage based on the low, medium, and high categories. The results of the analysis showed that of the seven-biology content tested in the limited trial of developing worksheets, the results obtained were for the low category the highest percentage of content in the biogeochemical cycle for all science process skills indicators. The medium category has the highest percentage of inference indicators for environmental balance, environmental change, environmental pollution, and environmental management. High category on environmental balance content; the highest percentage with indicators of observation, classification, prediction, and communication., environmental changes on indicators of observation, classification, prediction, and communication, pollution indicators of observation, prediction, and communication. The conclusion based on the results of this preliminary field testing is that students are able to demonstrate science process skills using worksheets with various categories, and from the seven-biology content tested, the biogeochemical cycle is considered the most difficult by students